Ascorbic and citric acids mitigate cadmium stress and reduce metal accumulation in spinach grown in alkaline calcareous soil - Saira Hameed; Muhammad Nadeem; Muhammad Ashar Ayub; Muhammad Shabaan; Usman Zulfiqar; Hossam S. El-Beltagi; Dilrabo Kodirova; Dilafruz Solieva; Abdumurod Sattarov; Mashael Daghash Alqahtani; Abdulrahman Alasmari (BioMetals, 2026)

Evaluation of Heavy Metal Tolerant Plant Growth Promoting Pseudomonas Strains for Improving the Growth of Eggplant (Solanum Melongena L.) under Lead (Pb) Stress - Uzma Ambreen; Muhammad Shabaan; Muhammad Junaid Sarwar; Mehreen Malik; Saira Sulaman; Hafiz Naeem Asghar; Usman Zulfiqar; Hossam S. El-Beltagi; Gamal Awad El-Shaboury; Arzu Bakhshaliyeva; Abdulrahman Alasmari (Water, Air, & Soil Pollution, 2026)

Exogenous Application of Nitrogen (N) and Potassium (K) Improves Drought Tolerance in Plants: A Review - Saira Sulaman; Muhammad Nadeem; Muhammad Shabaan; Sule Orman; Muhammad Anwar-ul-Haq; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)
With rising climate anomalies and deterioration of ecological balance, water shortage has emerged as a major environmental problem faced by mankind, which has considerably limited agricultural productivity worldwide. Drought stress generates an insidious hazard by destabilizing global hydrological cycle and due to its increased frequency, severity and associated adverse impacts on climate conditions, drought has obtained attention world over. Exposure to severe and acute drought stress disturbs physiological functioning of plants and inhibits the efficiency of photosynthetic system. As a result, lesser photosynthate production causes lower plant biomass and yield. Hence, it is imperative to sustain and improve plant growth and productivity under water shortage conditions to minimize its dreadful impacts. Current review summarizes the adverse impacts of drought stress on various agricultural crops, its alleviation strategies and various adaptations encountered by plants under drought stress. More importantly, current review emphasizes the beneficial roles played by macronutrients such as nitrogen (N) and potassium (K) in alleviating the adverse impacts of drought stress. As these essential nutrients have reportedly been involved in alleviating the negative impacts of drought stress on plant growth and therefore, major information in the current review article revolves around the N and K supply to the plant under drought stress. In addition, current review necessitates the use of optimum doses of N and K fertilizers to ensure maximum resource utilization efficiency and increased drought resilience.

Harnessing the Duo Effect of Plant Growth-Promoting Rhizobacteria and Organic Amendments in the Phytoremediation of Cadmium: a Review - Muhammad Junaid Sarwar; Muhammad Shabaan; Muhaimen Ayyub; Zahir Ahmad Zahir; Hafiz Naeem Asghar; Kashiuf Asif; Aqsa Shareef; Usman Zulfiqar (Journal of Soil Science and Plant Nutrition, 2025)

Ameliorative Effects of Silica on Growth, Antioxidant Response, and Metal Uptake in Chromium-Exposed Wheat - Khadija Ali; Muhammad Nadeem; Asia Khan; Rafia Mustafa; Muhammad Shabaan; Usman Zulfiqar; Sadam Hussain; Jawaher Alkahtani (Journal of Crop Health, 2025)

Synergistic Application of Bacterial Consortium and Organic Amendments Improves the Growth and Seed Quality of Mash Bean (Vigna Mungo L.) - Kashiuf Asif; Muhammad Shabaan; Waqas Mahmood; Hafiz Naeem Asghar; Zahir Ahmad Zahir; Usman Zulfiqar; Sadam Hussain; Walid Soufan (Journal of Soil Science and Plant Nutrition, 2024)

Integrated application of biochar and chemical fertilizers improves wheat (Triticum aestivum) productivity by enhancing soil microbial activities - Muhammad Abdullah Aziz; Khalid Saifullah Khan; Rabia Khalid; Muhammad Shabaan; Abdulaziz G. Alghamdi; Zafer Alasmary; Mosaed A. Majrashi (Plant and Soil, 2024)

Phosphorous (P)-Solubilizing Rhizobacteria Improve P Availability to Mung Bean via Enhanced Soil Phosphatase Activity and Improve Its Growth - Rabia Khalid; Aqsa Khalid; Muhammad Shabaan; Hafiz Naeem Asghar; Zahir Ahmad Zahir (Journal of Soil Science and Plant Nutrition, 2023)

Co-application of organic amendments and Cd-tolerant rhizobacteria for suppression of cadmium uptake and regulation of antioxidants in tomato - Muhammad Junaid Sarwar; Zahir Ahmad Zahir; Hafiz Naeem Asghar; Muhammad Shabaan; Muhaimen Ayyub (Chemosphere, 2023)